Upaya Meningkatkan Produksi Pada Line Machining Crankcase K-58 Dengan Menggunakan Total Productive Maintenance (TPM) dan Failure Mode and Efect Analysis (FMEA) - Muhazir, Achmad; Sinaga, Zulkani; Illahi, Firman (Universitas Teuku Umar, 2024)
This study aims to improve production achievement and minimize failures and losses that occur in the Machining Crankcase K-58 line at PT XYZ. The production target was not achieved due to the high frequency of setups on the Fine Boring machine, broken cutting tools, and the large number of product rejects during the production process. The analysis is carried out using the Total Productive Maintenance (TPM) method, namely by calculating the machine's KPI via OEE then identifying it based on the six big losses, so that the root cause of the damage can be identified, while Failure Mode and Effects Analysis (FMEA) is to identify losses based on the mode of damage that occurs. from the known value of the Risk Priority Number (RPN) of critical components that cause machine failure. Based on the calculation of Overall Equipment Effectiveness (OEE) for the year 2023, an OEE value of 76.2% was obtained. The highest value of the Six Big Losses was in the Reduced Speed Losses category, with a percentage of 14.21%. After improvements with the 8-pillar TPM approach, particularly through autonomous maintenance, the OEE value increased by 9.3% to 85.5% in April 2023. The Availability Rate reached 96.3%, the Performance Rate was 91.2%, and the Quality Rate was 97.4%. The improvements included the implementation of autonomous maintenance, kaizen, and planned maintenance, which successfully enhanced the efficiency and effectiveness of production in the Machining Crankcase K-58 line.